2008
DOI: 10.1104/pp.108.123273
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Onion Lachrymatory Factor Synthase Causes a Significant Change in the Sulfur Secondary Metabolite Profile    

Abstract: Through a single genetic transformation in onion (Allium cepa), a crop recalcitrant to genetic transformation, we suppressed the lachrymatory factor synthase gene using RNA interference silencing in six plants. This reduced lachrymatory synthase activity by up to 1,544-fold, so that when wounded the onions produced significantly reduced levels of tear-inducing lachrymatory factor. We then confirmed, through a novel colorimetric assay, that this silencing had shifted the trans-S-1-propenyl-L-cysteine sulfoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 45 publications
4
83
0
1
Order By: Relevance
“…HPLC analysis of LF produced in macerated onion bulb material demonstrated that the LF levels in LR11 transgenic onion (180 mg g Ϫ1 fresh mass) were reduced by half compared with those of wild-type controls (350 mg g Ϫ1 fresh mass). A similar extent of LF reduction were previously reported in the LFS silencing onions (Eady et al 2008). The reduced levels of lachrymatory sensation were consistent with the LFS suppression levels in the transgenic bulbs.…”
Section: Characteristics Of the Transgenic Onionssupporting
confidence: 75%
See 2 more Smart Citations
“…HPLC analysis of LF produced in macerated onion bulb material demonstrated that the LF levels in LR11 transgenic onion (180 mg g Ϫ1 fresh mass) were reduced by half compared with those of wild-type controls (350 mg g Ϫ1 fresh mass). A similar extent of LF reduction were previously reported in the LFS silencing onions (Eady et al 2008). The reduced levels of lachrymatory sensation were consistent with the LFS suppression levels in the transgenic bulbs.…”
Section: Characteristics Of the Transgenic Onionssupporting
confidence: 75%
“…These results indicate that a significant increase in thiosulfinate levels would require a reduction in LFS enzyme activity to approximately 1% or less than that of the wild-type control, as found in the bulbs from LR11 line. Eady et al (2008) reported a large accumulation of thiosulfinate in onion plants in which LFS enzyme activity was reduced by between 500-and 1500-fold compared to nontransgenic controls. Because the isomerization reaction catalyzed by LFS is presumably much faster than the spontaneous reactions forming thiosulfinate and pink pigments, the residual LFS enzyme activity found in the transgenic bulbs from LR21, LR22, and LR23 lines could have been high enough to limit the availability of 1-PS for thiosulfinate formation, but low enough to limit the rate of LF release below the threshold level for lachrymatory stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of 1-propenyl sulfenic acid to propanthial S-oxide (tear-inducing, lachrymatory factor, LF) is mediated by an enzyme, named lachrymatory factor synthase (LFS). Eady et al (2008) suppressed lfs gene by hpRNAi using 35S CaMV promoter reducing LFS activity in wounded onion resulting in the production of tearless onion.…”
Section: Allergen and Toxin Eliminationmentioning
confidence: 99%
“…In addition to plant biology studies, RNAi plays important and unique roles in crop genetic improvements (Auer and Frederick 2009;Baykal and Zhang 2010). RNA interference may achieve more significant crop improvements than conventional breeding, as illustrated by various important crop species with different improved traits (Liu et al 2002;Ogita et al 2003;Gilissen et al 2005;Le et al 2006;Bonfim et al 2007;Shi et al 2007;Dodo et al 2008;eady et al 2008;Flores et al 2008;Shimizu et al 2009). Many of these studies show that the RNAi-mediated silencing is inheritable, alleviating long-standing concerns about the RNAi inheritability.…”
Section: Introductionmentioning
confidence: 99%